IS OBESITY PHARMACOTHERAPY A LIFETIME COMMITMENT? A STRUCTURED REVIEW OF WEIGHT REGAIN AND STRATEGIES FOLLOWING INCRETIN CESSATION - Kornelia Domagała; Amanda Dolores Abramowicz; Magdalena Rumin; Olga Tatarata; Maja Osuch; Maciej Osuch; Anna Kiełboń; Martyna Jaciubek; Carmena Luty; Zuzanna Olga Reklewska (International Journal of Innovative Technologies in Social Science, 2026)
Background: The 2026 World Health Organization (WHO) guidelines formalize a major shift in metabolic medicine by characterizing obesity as a chronic, progressive, and relapsing neuroendocrine disease. While innovative incretin-based medical technologies - specifically GLP-1 and dual GIP/GLP-1 receptor agonists - have achieved weight-loss magnitudes previously reserved for invasive metabolic surgery, the long-term durability of these outcomes after treatment cessation remains a formidable socio-clinical challenge. Objective: This structured narrative review synthesizes contemporary evidence regarding weight-loss maintenance, the biological drivers of regain, and the systemic barriers to treatment persistence following the discontinuation of incretin-based therapies. Methods: A comprehensive search of major bibliographic databases (2011–2026) was conducted, integrating data from randomized withdrawal trials (STEP and SURMOUNT programs), large-scale meta-analyses, and diverse real-world evidence (RWE). Results: Evidence indicates that statistically significant weight regain can emerge as early as 8 weeks post-discontinuation, with substantial recovery of lost weight typical within 12 months. This rebound is primarily mediated by a biological “energy gap” of approximately 120 kcal per kilogram lost, driven by a combination of adaptive thermogenesis (reduced energy expenditure) and heightened orexigenic signaling. Crucially, real-world data reveal a significant "persistence gap," with 50–67% of patients discontinuing therapy within the first year due to economic barriers, global supply instabilities, and tolerability issues. Conclusions: Effective obesity management requires a transition from short-term interventions to a lifelong "chronic care continuum." Future strategies must prioritize the preservation of fat-free mass, implement intensified monitoring protocols (specifically the 25% regain threshold), and promote a systemic reframing of pharmacotherapy as a permanent metabolic stabilizer rather than a transient cure.